2016
DOI: 10.14238/pi45.1.2005.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pulmonary functions of thalassemic and of healthy children

Abstract: Objectives The aim of this study was to compare some pulmonary functions of thalassemic patients and those of normal children. Factors correlated with lung dysfunction were assessed.Methods This cross-sectional study compared some pulmonary functions of thalassemic patients with those of healthy children. The study was performed in the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Pre-and post-transfusion hemoglobin levels of the thalassemic subjects were determined. Other data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…No relation between restrictive pattern and serum ferritin levels was observed in the present study which was in line with other studies. 2,3,[11][12][13][14][15] However, a study conducted by Kanj et al showed that PFT (restriction pattern) correlated with serum ferritin. 16 Ferritin may not accurately reflect the total iron burden, and its levels change during the process of chelation.…”
Section: Discussionmentioning
confidence: 99%
“…No relation between restrictive pattern and serum ferritin levels was observed in the present study which was in line with other studies. 2,3,[11][12][13][14][15] However, a study conducted by Kanj et al showed that PFT (restriction pattern) correlated with serum ferritin. 16 Ferritin may not accurately reflect the total iron burden, and its levels change during the process of chelation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Di Jakarta pada tahun 1998 Wirjodiardjo M melakukan penelitian pada anak sekolah usia 6-14 tahun, mendapatkan nilai APE yang diperiksa dengan MWPFM lebih besar dibandingkan spirometer elektronik sehingga diperlukan tabel konversi. 11 Said M (2004) melakukan penelitian uji faal paru pada anak thalasemia dibandingkan dengan anak sehat, didapatkan nilai uji fungsi paru anak thalasemia lebih rendah daripada anak sehat. 12 Penelitian uji fungsi paru pada anak jalanan belum pernah dilakukan.…”
unclassified
“…11 Said M (2004) melakukan penelitian uji faal paru pada anak thalasemia dibandingkan dengan anak sehat, didapatkan nilai uji fungsi paru anak thalasemia lebih rendah daripada anak sehat. 12 Penelitian uji fungsi paru pada anak jalanan belum pernah dilakukan.…”
unclassified